Implementation of Thematic Learning in Increasing Cognitive Development and Children Language in Raudhatul Atfhal Rahmat Islamiyah Medan - Tien Rafida; Jamilah Jamilah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The objectives of this study are: (1) thematic learning planning in Raudhatul Athfal Rahmat Islamiyah Medan, (2) implementation of thematic learning in improving children's cognitive and language development in Raudhatul Athfal Rahmat Islamiyah Medan, (3) evaluation of thematic learning in Raudhatul Athfal Rahmat Islamiyah Medan , and (4) supporting and inhibiting factors for the implementation of thematic learning in Raudhatul Atfhal Rahmat Islamiyah Medan. This research method is qualitative conducted at Raudhatul Atfhal Rahmat Islamiyah Medan. Instrument data collection is done by interview, observation, and documentation. Data analysis techniques used Miles and Huberman models, namely data reduction, data presentation and conclusion. The research findings show: (1) Thematic learning planning conducted by Raudhatul Atfhal Rahmat Islamiyah Medan teacher by preparing the learning implementation plan at the beginning of the semester by referring to the applicable Raudhatul Atfhal curriculum, (2) implementing thematic learning at Raudhatul Atfhal Rahmat Islamiyah The terrain is done with varied learning methods by using various kinds of games such as remembering names, achievement games, motion games, construction games and also playing roles, (3) evaluation of learning on thematic learning at Raudhatul Atfhal Rahmat Islamiyah Medan by giving a portfolio, in this case evaluated changes in behavior, children can also experience cognitive and language improvement after participating in the thematic learning process, and (4) there are supporting and inhibiting factors for the implementation of thematic learning but the obstacles can still be well addressed.